El programa de cursos libres de la Dirección de Extensión Universitaria de la Universidad Estatal a Distancia (UNED) - Venegas Bonilla, Grace (2011)
This article offers a theoretical summary of the fundamentals of UNED’s extension programs based on an analysis of thse socio-philosophical ideas that allow us to argue for an implementation of the Free Course Program, and to revise Villarini (1996) and Tunnermann’s (1999) proposals for higher education in order then to articulate university actions which respond to the cultural, social and historical reality of Costa Rican society. Based on the information systematized in this article, the study seeks to propose theoretical and philosophical principles that will allow us to reflect on university issues in order to offer a pertinent response to the demands by different groups from a non-formal education perspective, in this case, from the Free Course Program of UNED’s Extension Division. This aspect will be developed in a future article.